A descriptive study of the participation of children and adolescents in activities outside school. Issue 1 (December 2016) - Imms, Christine; Froude, Elspeth; Adair, Brooke; Shields, Nora
Abstract Background Knowledge about patterns of participation can be used to highlight groups of children and adolescents with low attendance, or low involvement in activities and who may therefore be at risk of mental or physical health concerns. This study used theChildren's Assessment of Participation and Enjoyment (CAPE) and thePreferences for Activity of Children (PAC) to describe the patterns of participation of children and adolescents in activities outside mandated school in Victoria, Australia. Methods A cross-sectional survey of Victorian children and adolescents was conducted. Eligible participants were aged 6 to 18 years, enrolled in mainstream schools, with sufficient English language skills to complete the questionnaires. Parents of participants completed a demographic questionnaire. Sample representativeness was assessed against Victorian population statistics for gender, school type, language spoken at home and socio-economic status. Data for the CAPE and PAC were summarised using descriptive statistics. Patterns of activity diversity by age were assessed using curve estimation, with additional analyses to describe differences between genders. Results Of 9337 potential participants targeted through school advertising, 512 agreed (5.5 % consent rate), and 422 questionnaires were returned (82.4 % response rate). The sample was representative in terms of gender and language. Compared to the Victorian population, a slightly higher proportion of participants attended Government and Catholic schools and there was evidence of marginally greater socioeconomic resources than the population average. A broad range of recreational, active physical, social, skill-based and self-improvement activities were completed by all age groups. There was a reduction in the number and enjoyment of recreational activities with increasing age. In contrast, there was relative stability in intensity, frequency and preference scores across the age-groups for all activity types. Female participants typically took part in more activities (higher diversity scores), more intensely, with higher enjoyment and had higher preferences for each activity type than males, with the exception of active physical activities. Conclusions This study provides evidence of the participation patterns of typically developing children and adolescents in activities outside school. The findings have implications for researchers, clinicians and educators for comparative purposes and to inform future research.